2004
DOI: 10.1016/j.jcta.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Long cycles in the middle two layers of the discrete cube

Abstract: We prove that the middle two layers of the cube Q 2rþ1 contain a cycle of length ð1 À oð1ÞÞ2 2rþ1 r À Á : Our methods can also be used to show that the odd graph O k contains a cycle of length ð1 À oð1ÞÞjV ðO k Þj:One of our tools, giving a Hamilton cycle in the cube with the minimum number of 'changes of direction', may be of independent interest. r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…, k}. This approximate version of the conjecture is similar in spirit to the line of work [Sav93,FT95,SW95,Joh04] that preceded the proof of Theorem 1. 1.2.…”
supporting
confidence: 60%
“…, k}. This approximate version of the conjecture is similar in spirit to the line of work [Sav93,FT95,SW95,Joh04] that preceded the proof of Theorem 1. 1.2.…”
supporting
confidence: 60%
“…Recently, it was shown that M 2k+1 is "asymptotically Hamiltonian" in the following sense [7]: There is a constant c such that for all k, M 2k+1 has a cycle of length at least (1 − c/ √ k)V (M 2k+1 ). The existence proof in [7] does not attempt to estimate c. To improve the bound in Theorem 1 for, say all k < 5600, would require a value of c < 10.…”
Section: Introductionmentioning
confidence: 99%
“…Savage and Winkler [15] showed that if B k has a Hamiltonian cycle for k ≤ h, then B k has a cycle containing a fraction 1 − ε of the graph vertices for all k, where ε is a function of h. For example, since B k has a Hamiltonian cycle for 2 ≤ k ≤ 18, then B k has a cycle containing at least 86.7% of the graph vertices, for any k ≥ 2. Johnson [8] showed that both B k and O k have cycles containing (1 − o(1))|V | vertices, where |V | is the number of vertices in the graph. Johnson and Kierstead [9] used matchings of B k to show that O k has not only a 2-factor (spanning collection of cycles), but also a 2-factorisation.…”
Section: Introductionmentioning
confidence: 99%